Strategies for becoming a more desirable mate: evidence from Lithuania - Apostolou, Menelaos; Sullman, Mark; Markšaitytė, Rasa; Šeibokaitė, Laura; Lajunen, Timo Juhani (Frontiers in Psychology, 2024)
Introduction Mate-seekers employ several strategies to become more attractive as mates. In the present study, we examined the use of 10 strategies for becoming more desirable as a mate in the Lithuanian cultural context. Methods Using a sample of 295 Lithuanian-speaking participants, we explored the frequency and types of strategies employed to enhance mate appeal. Results The most frequently used strategy was “Enhance looks,” followed by “Show off abilities and talents” and “Demonstrate similarity.” The least used strategies were “Show off and exaggerate wealth” and “Drastic appearance changes.” The 10 strategies could be classified into two domains or main strategies, with participants indicating a more frequent use of “Develop and demonstrate desirable traits” followed by “Deceive about undesirable traits.” Additionally, sex differences and age differences were identified for several strategies. Discussion The findings highlight the prominence of certain strategies over others in the Lithuanian context, with a notable emphasis on developing and demonstrating desirable traits. The study also reveals variations in strategy use based on sex and age, suggesting that these factors influence mate-seeking behaviors.